Legality and legitimacy in global affairs - Falk, Richard A.; Juergensmeyer, Mark.; Popovski, Vesselin (Oxford : Oxford University Press, 2012)
This text focuses on the problematic relationship between legality and legitimacy when a nation (or nations) intervene in the work of other nations.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: International law